The impact of night shift work on cortisol secretion - Strawińska, Aleksandra; Karol , Michał; Koseska, Kamila; Borowicz, Jan; Górecki , Bartosz; Kloch , Kinga; Romaniuk, Patryk; Lohin, Mariia-Khrystyna; Bednarczyk , Małgorzata (Quality in Sport, 2026)
Night-shift work poses significant challenges to human health, largely through disruption of circadian rhythms and dysregulation of cortisol secretion. Cortisol, a key glucocorticoid, regulates metabolism, immune function, and stress responses, following a distinct diurnal pattern characterized by a morning peak and gradual decline throughout the day. Night-shift work alters this rhythm, often causing blunted cortisol awakening responses, elevated evening cortisol levels, and overall circadian misalignment. These hormonal disturbances contribute to a spectrum of adverse health outcomes, including metabolic dysregulation (insulin resistance, hyperglycemia, obesity), cardiovascular disorders (hypertension, atherosclerosis, increased cardiovascular mortality), impaired cognitive function, and heightened susceptibility to mood disorders such as anxiety and depression. Sleep disruption further exacerbates cortisol dysregulation and associated physiological and psychological effects. Understanding the mechanisms linking night-shift work to cortisol rhythm alterations is crucial for developing interventions aimed at mitigating health risks in shift-working populations. This review synthesizes current evidence on the effects of night-shift work on cortisol dynamics and the broader implications for metabolic, cardiovascular, and mental health.